Improving Adolescent Mental Health Through Psychoeducation and Peer Support - Erli Effendi (Bakti Nusantara Pengabdian Masyarakat Indonesia, 2026)
Background: Adolescent mental health has become a major public health concern, as academic demands, social pressure, and psychosocial development may increase vulnerability to stress and emotional problems. Community-based promotive and preventive strategies are therefore needed to strengthen adolescents’ mental health literacy and coping capacity. Objective: This study aimed to improve adolescent mental health through psychoeducation and peer support interventions. Methods: A community-based promotive–preventive program was conducted among 72 adolescents. The intervention combined interactive psychoeducation, small-group discussions, stress-coping simulations, role play, and the formation of peer support groups. Participants were purposively recruited from educational and youth community settings. Program evaluation was carried out using a pre–post assessment of mental health knowledge, participant observation, and feedback on the implementation process. Respondent characteristics, including age, sex, educational level, main activity, and prior exposure to mental health education, were also described. Results: Most participants were aged 16–18 years (50.0%), female (58.3%), enrolled in senior high school/vocational school (52.8%), and had never previously received mental health education (69.4%). Following the intervention, the proportion of adolescents with good mental health knowledge increased from 25.0% to 63.9%, while the proportion with poor knowledge declined from 36.1% to 8.3%. The program also facilitated the establishment of peer support groups that promoted emotional openness, constructive communication, and stronger psychological coping among participants. Conclusion: Psychoeducation integrated with peer support was effective in improving adolescent mental health literacy and strengthening psychosocial resilience. Sustainable implementation, wider target coverage, and longer-term monitoring are recommended to optimize the impact of community-based adolescent mental health programs.